ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KOMPETENSI PESERTA DIDIK - Haidah, Masaad; Rohiyatun, Baiq; Najwa, Lu’luin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The Merdeka Curriculum is an educational policy designed to provide flexibility for schools in developing students’ potential based on their characteristics, interests, and talents. This curriculum emphasizes student-centered learning, collaboration, and project-based approaches to strengthen the Pancasila Student Profile. This study aims to examine the implementation of the Merdeka Curriculum at SMA Negeri 2 Mataram and to identify the supporting and inhibiting factors in improving students’ competencies. This research employs a qualitative approach with a descriptive method. The informants include the vice principal for curriculum affairs, subject teachers, and twelfth-grade students. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Merdeka Curriculum has been carried out gradually and systematically. Teachers refer to Learning Outcomes, develop Learning Objective Flows, and apply differentiated learning strategies. The Pancasila Student Profile Strengthening Project plays a role in fostering students’ character, creativity, and collaboration. Its implementation is supported by school commitment, teacher readiness, and adequate facilities, although challenges remain, such as limited instructional time and differences in students’ abilities. ABSTRAK Kurikulum Merdeka merupakan kebijakan pendidikan yang memberikan keleluasaan kepada satuan pendidikan dalam mengembangkan potensi peserta didik sesuai karakteristik, minat, dan bakatnya. Kurikulum ini menekankan pembelajaran berpusat pada peserta didik, kolaborasi, serta penggunaan pendekatan berbasis proyek untuk memperkuat Profil Pelajar Pancasila. Penelitian ini bertujuan mengkaji implementasi Kurikulum Merdeka di SMA Negeri 2 Mataram serta mengidentifikasi faktor pendukung dan penghambat dalam meningkatkan kompetensi peserta didik. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Informan terdiri atas wakil kepala sekolah bidang kurikulum, guru, dan siswa kelas XII. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Merdeka telah berjalan secara bertahap dan sistematis. Guru mengacu pada Capaian Pembelajaran, mengembangkan Alur Tujuan Pembelajaran, serta menerapkan pembelajaran berdiferensiasi. Projek Penguatan Profil Pelajar Pancasila berperan dalam mengembangkan karakter, kreativitas, dan kolaborasi siswa. Keberhasilan didukung oleh komitmen sekolah, kesiapan guru, dan fasilitas, meskipun masih terdapat kendala seperti keterbatasan waktu dan perbedaan kemampuan siswa.